Novel electrochemical genosensor for Zika virus based on a poly-(3-amino-4-hydroxybenzoic acid)-modified pencil carbon graphite electrode - da Fonseca Alves, Rafael [UNESP]; Franco, Diego Leoni; Cordeiro, Marli Tenório; de Oliveira, Ernesto Marques; Fireman Dutra, Rosa Amalia; Del Pilar Taboada Sotomayor, Maria [UNESP] (Elsevier, 2019)
The Zika virus has recently emerged as a major worldwide threat because it induces microencephaly and other brain damage in babies born to infected mothers. Epidemiological monitoring of infection has been hampered by the lack of reliable tests capable of distinguishing between Zika and other Flavivirus infections, especially the dengue virus. The present work describes the electrochemical modification of pencil carbon graphite electrodes with a material derived from 3-amino-4-hydroxybenzoic acid. Solutions were prepared in acid medium and the material formed showed insulating behavior. Optical and electrical data suggested that carboxyl groups did not participate in the reaction mechanism. FT-IR spectra indicated that these groups were retained, enabling the proposal of a mechanism based on the data obtained. The material formed was used for immobilization of the ssDNAzv aminated oligonucleotide. Detection of the hybridization was based on the Δip resulting from the higher electrostatic repulsion of [Fe(CN)6]3−, caused by the increase of phosphates by addition of the complementary target sequence. The system showed a good linear correlation coefficient (r² = 0.997), with satisfactory selectivity and reproducibility, a low limit of detection (25.4 pM), and precision (RSD) of 3.1%, using real samples of human serum enriched with total extract of Zika virus RNA. Tests of the system using the total RNA extracted from dengue virus types 2 and 3 cultures showed little difference in the observed current, hence confirming the specificity of the system. These findings demonstrated the potential of the proposed biosensor.
Keywords: 3-Amino-4-hydroxybenzoic acid polymer; Electrochemical genosensor; Pencil graphite; Zika virus